Hypertriglyceridemic waist - a simple clinical tool to detect cardiometabolic risk: comparison with harmonized definition of metabolic syndrome - Vaverková, H; Karásek, D; Novotný, D; Halenka, M; Orság, J; Slavík, L (Physiological research, 2015)
With the increasing prevalence of obesity and especially abdominal obesity, a simple clinical tool is needed that identifies the cardiometabolic risk for cardiovascular disease and type 2 diabetes. The aim of our study was to evaluate a broad spectrum of metabolic variables and IMT in subjects with and without hypertriglyceridemic waist (HTGW) and compare it with the harmonized definition of metabolic syndrome (MS) with both a higher (MS-I) and lower waist circumference (MS-II) for Europids. We enrolled 607 asymptomatic dyslipidemic subjects (295 men and 312 women) into our cross-sectional study. The subjects with HTGW had an atherogenic lipid profile (significantly higher triglycerides, AIP, non-HDL-C, lower HDL-C and ApoA-1, and the women also higher TC and ApoB), increased markers of insulin resistance (insulin, HOMA, C-peptide, proinsulin), inflammation (hsCRP), thrombosis (fibrinogen, PAI-1), SBP and DBP, and lower adiponectin (p<0.05-0.001 for all). These risk factors were entirely similar in HTGW, MS-I and MS-II. Age-adjusted IMT was significantly higher only in the women with HTGW but this significance disappeared after further adjustment for TC, SBP, and smoking. Our results support the routine use of HTGW as a simple and inexpensive screening tool to detect subjects at increased cardiometabolic risk in clinical practice.
Keywords: Cross-Sectional Studies; Metabolic Syndrome; Middle Aged; mužské pohlaví; průřezové studie; Adult; Hypertriglyceridemic Waist; Cardiovascular Diseases; ženské pohlaví; metabolický syndrom; Humans; hypertriglyceridemický pas; lidé středního věku; rizikové faktory; dospělí; Female; Risk Factors; kardiovaskulární nemoci; lidé; Male